PENGARUH TEKANAN EKSTERNAL, KETIDAKPASTIAN LINGKUNGAN, KOMITMEN MANAJEMEN, DAN AKSESIBILITAS LAPORAN KEUANGAN TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi pada Satuan Kerja Perangkat Daerah Kabupaten Kampar) - M. Ade Kasfauzi; M. Rasuli '; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to analyze the influence of external pressure, environment uncertainty, management commitment, and accessibility of financial statements on implementation of tranparency of financial report in Kampar regency. This research was carried out on financial management of each SKPD in Kampar regency. Samples obtained were amount to 104 person with purposive sampling manner. The data of this research using primary data direcly through a questionnaire then and the data analysis user multiple linear regression by SPSS 20. The research indicates that: external pressure has significant effect on the implementation financial report transparency, where the significant value are 0,026<0,05. Environmental uncertainly has not significant effect on transparency of financial reporting, where the significant value are 0,547>0,05. Management commitment has significant effect on the implementation financial report transparency, where the significant value are 0,027<0,05. Accessibility of financial statements has significant effect on the implementation financial report transparency, where the significant value are 0,025<0,05.Keyword: external pressure, environment uncertainty, management commitment, accessibility of financial statements, and transparency.